Coincidence Point Theorems for Geraghty-Type Contraction Mappings in Generalized Metric Spaces: Atit Wiriyapongsanon, Narawadee Phudolsitthiphat - Team, Support (Thai Journal of Mathematics, 2023)
In 2005, Jleli and Samet introduced a new concept of generalized metric spaces which cover standard metric spaces, b-metric spaces and dislocated metric spaces. In this paper, we prove some coincidence theorems for Geraghty-type contraction mappings in partially ordered generalized metric spaces. Moreover, we obtain a coupled coincidence point result as a corollary of our main theorem. Finally, we give an example to support our results.